The Pains of Sharing Pleasure: Imag(in)ing Motherhood on Pinterest - Lakämper, Judith (Journal of the Motherhood Initiative for Research and Community Involvement, 2015)
Contemporary experiences of motherhood take stage at the intersection between ideologies of intensive mothering, which demand an exclusive orientation towards the needs of the child, and new individualism, which prescribes a focus on the self, and a continuous need to re-invent self-identity physically, psychologically, and professionally. This essay argues that while Pinterest provides a forum for women to experiment with a variety of rapidly revisable self-representations, it simultaneously functions to reinforce compartmentalized idealizations of motherhood in the form of imagery from a regressive and repressive cultural archive. The ideal user is a post-feminist subject who celebrates the freedom to enjoy visual pleasure uncritically, thereby participating in the continued dissemination of unattainable ideals of motherly perfection. Thus, as a site where the conflict between different demands becomes tangible via the use of images, Pinterest offers an important window into the complexity of contemporary experiences of motherhood.